Comparing Four Question Formats in Five Languages for On-Line Consumer Surveys - Denis Richard Seninde; Edgar Chambers (Methods and Protocols, 2020)
Question formats are critical to the collection of consumer health attitudes, food product characterizations, and perceptions. The information from those surveys provides important insights in the product development process. Four formats based on the same concept have been used for prior studies: Check-All-That-Apply (CATA), Check-All-Statements (CAS), Rate-All-That-Apply (RATA), and Rate-All-Statements (RAS). Data can vary depending on what question format is used in the research, and this can affect the interpretation of the findings and subsequent decisions. This survey protocol compares the four question formats. Using a modified version of the Eating Motivation Survey (EMS) to test consumer eating motivations for five food items, each question format was translated and randomly assigned to respondents (N = 200 per country per format) from Brazil (Portuguese), China (Mandarin Chinese), India (Hindi or English), Spain (Spanish), and the USA (English). The results of this survey should provide more understanding of the differences and similarities in distribution of data for the four scale formats. Also, the translations and findings of this survey can guide marketers, sensory scientists, product developers, dieticians, and nutritionists when designing future consumer studies that will use these question formats.